3-Benzoyl-1,1-dibenzylthiourea - Gunasekaran, N.; Karvembu, R.; Ng, S.W.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
Two independent thiourea molecules comprise the asymmetric unit of the title compound, C(22)H(20)N(2)OS. The central N-C(=S)N(H)C(=O) atoms in each molecule are virtually superimposable and each is twisted [C-N-C-S torsion angles = 121.3 (3) and -62.3 (4)degrees]. The molecules differ only in terms of the relative orientations of the benzyl benzene rings [major difference between the C-N-C-C torsion angles of -146.6 (3) and -132.9 (3)degrees]. The presence of N-H center dot center dot center dot S hydrogen bonding leads to the formation of supramolecular chains along the a axis. These are consolidated in the crystal packing by C-H center dot center dot center dot O interactions. The crystal was found to be a combined non-merohedral and racemic twin (twin law (1) over bar 00/0 (1) over bar0/001), with the fractional contribution of the minor components being approximately 9 and 28%.